2015
DOI: 10.1097/md.0000000000001617
|View full text |Cite
|
Sign up to set email alerts
|

Increased Klk9 Urinary Excretion Is Associated to Hypertension-Induced Cardiovascular Damage and Renal Alterations

Abstract: Early detection of hypertensive end-organ damage and secondary diseases are key determinants of cardiovascular prognosis in patients suffering from arterial hypertension. Presently, there are no biomarkers for the detection of hypertensive target organ damage, most outstandingly including blood vessels, the heart, and the kidneys.We aimed to validate the usefulness of the urinary excretion of the serine protease kallikrein-related peptidase 9 (KLK9) as a biomarker of hypertension-induced target organ damage.Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These include the maleate model and the megalin knock-out model. Acute administration of sodium maleate uncouples proximal transmembrane transport and inhibits proximal reabsorption [ 34 , 35 , 36 ], leading to increased urinary excretion of a variety of protein biomarkers in the ultrafiltrate, with no effect on renal structures [ 26 , 34 , 37 , 38 , 39 , 40 ]. A very similar scenario is generated by knocking out megalin [ 41 ], an essential member of the proximal multiligand binding receptor endocytic complex responsible for protein reclamation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include the maleate model and the megalin knock-out model. Acute administration of sodium maleate uncouples proximal transmembrane transport and inhibits proximal reabsorption [ 34 , 35 , 36 ], leading to increased urinary excretion of a variety of protein biomarkers in the ultrafiltrate, with no effect on renal structures [ 26 , 34 , 37 , 38 , 39 , 40 ]. A very similar scenario is generated by knocking out megalin [ 41 ], an essential member of the proximal multiligand binding receptor endocytic complex responsible for protein reclamation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…KLK9 gene expression has also been related to non-malignant diseases. Recent studies associate KLK9 expression patterns with cardiac hypertrophy and hypertension-induced target organ damage [10], psoriatic lesions [11] and complications in asthma patients [12]. In general, KLK9-related studies are still very few.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of cancer cell lines revealed that KLK9 is constitutively expressed in breast, ovarian and lung cancer [9]. Recent studies associate KLK9 expression patterns with non-malignant diseases, such as cardiac hypertrophy and hypertension-induced target organ damage [10] psoriatic lesions [11] and complications in asthma patients [12]. …”
Section: Introductionmentioning
confidence: 99%